Prior exposure of Arabidopsis seedlings to mechanical stress heightens jasmonic acid-mediated defense against necrotrophic pathogens - Brenya, Eric (BMC Plant Biol, 2020)
BACKGROUND: Prolonged mechanical stress (MS) causes thigmomorphogenesis, a stress acclimation response associated with increased disease resistance. What remains unclear is if; 1) plants pre-exposed to a short period of repetitive MS can prime defence responses upon subsequent challenge with necrotrophic pathogens, 2) MS mediates plant immunity via jasmonic acid (JA) signalling, and 3) a short period of repetitive MS can cause long-term changes in gene expression resembling a stress-induced memory. To address these points, 10-days old juvenile Arabidopsis seedlings were mechanically stressed for 7-days using a soft brush and subsequently challenged with the necrotrophic pathogens, Alternaria brassicicola, and Botrytis cinerea. Here we assessed how MS impacted structural cell wall appositions, disease symptoms and altered gene expression in response to infection. RESULTS: The MS-treated plants exhibited enhanced cell wall appositions and jasmonic acid (JA) accumulation that correlated with a reduction in disease progression compared to unstressed plants. The expression of genes involved in JA signalling, callose deposition, peroxidase and phytoalexin biosynthesis and reactive oxygen species detoxification were hyper-induced 4-days post-infection in MS-treated plants. The loss-of-function in JA signalling mediated by the JA-insensitive coronatine-insensitive 1 (coi1) mutant impaired the hyper-induction of defense gene expression and promoted pathogen proliferation in MS-treated plants subject to infection. The basal expression level of PATHOGENESIS-RELATED GENE 1 and PLANT DEFENSIN 1.2 defense marker genes were constitutively upregulated in rosette leaves for 5-days post-MS, as well as in naïve cauline leaves that differentiated from the inflorescence meristem well after ceasing MS. CONCLUSION: This study reveals that exposure of juvenile Arabidopsis plants to a short repetitive period of MS can alter gene expression and prime plant resistance upon subsequent challenge with necrotrophic pathogens via the JA-mediated COI1 signalling pathway. MS may facilitate a stress-induced memory to modulate the plant’s response to future stress encounters. These data advance our understanding of how MS primes plant immunity against necrotrophic pathogens and how that could be utilised in sustainable agricultural practices.